Marshall Olkin Distributions - Advances in Theory and Applications Bologna, Italy, October 2013 - Cherubini, Umberto; Durante, Fabrizio; Mulinacci, Sabrina (Springer Proceedings in Mathematics & Statistics,, 2015)
This book presents the latest advances in the theory and practice of Marshall-Olkin distributions. These distributions have been increasingly applied in statistical practice in recent years, as they make it possible to describe interesting features of stochastic models like non-exchangeability, tail dependencies and the presence of a singular component. The book presents cutting-edge contributions in this research area, with a particular emphasis on financial and economic applications. It is recommended for researchers working in applied probability and statistics, as well as for practitioners interested in the use of stochastic models in economics. This volume collects selected contributions from the conference "Marshall-Olkin Distributions: Advances in Theory and Applications," held in Bologna on October 2-3, 2013.